2017
DOI: 10.5194/nhess-17-1375-2017
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of sensitivity analysis testing by applying the DRASTIC and fuzzy optimization methods to assess groundwater vulnerability to pollution: the case of the Senegal River basin in Mali

Abstract: Abstract. Vulnerability to groundwater pollution in the Senegal River basin was studied by two different but complementary methods: the DRASTIC method (which evaluates the intrinsic vulnerability) and the fuzzy method (which assesses the specific vulnerability by taking into account the continuity of the parameters). The validation of this application has been tested by comparing the connection in groundwater and distribution of different established classes of vulnerabilities as well as the nitrate distributi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Given the paucity of data and the possible limitations in the specificity of the DRAS-TIC method to the reality of the study area, an improved approach could be to modify the classical model (e.g. V-DRASTIC) or combine it with other developed models as in the entropy-weighted fuzzy DRASTIC method (Souleymane and Zhonghua, 2017).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the paucity of data and the possible limitations in the specificity of the DRAS-TIC method to the reality of the study area, an improved approach could be to modify the classical model (e.g. V-DRASTIC) or combine it with other developed models as in the entropy-weighted fuzzy DRASTIC method (Souleymane and Zhonghua, 2017).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Areas densely covered mainly by deeply rooted tree vegetation, promote evaporation at the expense of infiltration (Schilling et al, 2006). The rates, mostly based on literature (Preeja et al, 2011;Senanayake et al, 2016;Suganthi et al, 2013), are presented in Table 1 and applied to create the map in Fig. 2e.…”
Section: Land Use/land Covermentioning
confidence: 99%
“…Due to the importance of studying aquifer vulnerability in groundwater resources management, many studies have been conducted in this regard, for example, Souleymane and Zhonghua assessed groundwater vulnerability to pollution in Senegal River basin using DRASTIC and fuzzy optimization methods. They found that the vadose zone is the main parameter which affects groundwater vulnerability to pollution while net recharge contributes least to pollution in the study area (18). In another study, the chemical quality of groundwater of Orzooiyeh plain, southeast of Iran, was assessed.…”
Section: Introductionmentioning
confidence: 94%
“…Also, an innovative tabular method has been proposed to deal with the sensitivity analysis of fully FLP problems by Singh [32] involving a detailed study of different SA methods for building energy models considering the small residential building. A novel method of sensitivity analysis has been evolved by Keita [33] to identify and confirm the main parameters which influence the groundwater vulnerability to pollution with fuzzy optimization for the case of the Senegal River basin in Mali. From the literature, it is observed that the local and global sensitivity analysis methods are still applied in evaluating the robustness of a model.…”
Section: Introductionmentioning
confidence: 99%